Analisis Penggunaan Media Pembelajaran Macromedia Flash dan Design Grafis pada Mata Pelajaran Animasi terhadap Kreativitas Siswa SMK Pasundan 1 Kota Serang - Tomi Bustomi; Marini Marini; Firlly Aulia; Rita Fadilah; Fina Alfiyanti; Anton Nasrullah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
A course of learning requires appropriate learning media to make it easier for students to achieve abilities. For this reason, this research was conducted with the aim of testing and analyzing the use of learning media in the form of macromedia flash and graphic design in animation courses. The end result leads to an increase in student creativity. This study utilized a quantitative approach with data obtained from a questionnaire technique containing some information about the research being conducted. Then the results will be analyzed with multiple linear regression to find out which media has more influence on increasing their creativity. The results show that the use of macromedia flash media has a more positive effect on increasing student creativity in animation courses compared to the use of graphic design. While the use of graphic design has no influence on student creativity. But simultaneously or combined have the effect of increasing their creativity. While the final result is 71% capable of influencing student creativity and the remaining 29% is influenced by other factors. For this reason, overall the selection of the right learning media will provide an increase in the creative abilities of students at SMK Pasundan 1 Kota Serang.